Pharmacotherapy for Behçet’s Disease and the Risk of Malignancy - Huang, Mao-Xin; Wang, Cai-Yun; Guo, Jin-Yan; Li, Jian-Hao; Li, Xiao-Hong; Zhang, Jiang-An; Yu, Jian-Bin (Frontiers in Pharmacology, 2021)
Background: Behçet’s disease (BD) is associated with an increased risk of cancer. Few reports have been published on the relationship between drug exposure and the risk of cancer in patients with BD. Herein, we explored the relationship between pharmacologic interventions for BD and the risk of cancer. Methods: we carried out a retrospective nested case-control study in a cohort of BD patients from attending our institution. Among 1,148 patients, 22 cancer patients were individually 1:2 matched to 44 cancer-free controls. The following biochemical indicators were evaluated: routine blood analysis, liver and kidney function tests, inflammatory indexes, blood gas analysis, blood electrolyte and previous pharmacologic interventions to manage BD including systemic glucocorticoids, methotrexate, cyclosporine-A, azathioprine, cyclophosphamide (CYC), and thalidomide, which are considered the primary medicines used for the management of BD. Results: Among the 22 BD patients with cancers, myelodysplastic syndrome (MDS) (22.72%) was the most common type. Furthermore, CYC administration was significantly higher in BD patients with cancer compared with the cancer-free matched control group. Further, we observed that complement 4 (C4) (odds ratio [OR] = 0.0001, 95% confidence interval [CI]: 0.001–0.065) and hemoglobin (Hb) (OR = 0.891, 95% CI: 0.795–0.998) levels were independent protective factors for predicting cancer risk in BD patients on multivariate analyses. Conclusion: Our study revealed that CYC was associated with a high risk of cancer in BD patients. Furthermore, C4 and Hb are independent protective factors for oncogenesis in BD patients. These findings may provide references and suggestions for clinicians to select appropriate treatments and for the early recognition of high-risk patients to reduce cancer incidence in BD patients.